The Effect of E-wallet and Sales Promotion on Purchasing Decisions - Subagiyo; Adriani Gustia; Donny Oktavian Syah (International Publisher, 2022)
E-wallet is an electronic device, online service, or software program that allows one party to make electronic transactions with another party bartering digital currency units for goods and services. This can include purchasing items on-line with a computer or using a smartphone to purchase something at a store. Currently in Indonesia there are many kinds of E-Wallets including; DOKU, BBM money bank Permata, cash XL, Telkomsel T-Cash, CIMB Niaga Mobile Account, and so on. One example of an E-wallet is Gopay, inaugurated in April 2016 that can be used in all payment transactions in the Gojek application. This study aims to investigate the effects of E-wallet and Sales Promotion of Hop Hop Purchasing Decisions among high school students in the city of North Jakarta. This is explanatory research using probability sampling method and using a questionnaire on Google Form for collecting data. The sample used is 100 respondents from high school students who use the GOPAY electronic wallet to buy Hop Hop in the city of North Jakarta. This research uses quantitative analysis: validity, reliability, classic assumptions, correlation coefficient, determination coefficient, simple and multiple linear regression, hypothesis significance of t test and F test. The results of multiple linear regression analysis show that there was an effect of E-wallet and Sales Promotion on purchasing decisions. The variable correlation coefficient of the use of E-wallet and Sales Promotion on the GOPAY E-wallet has a strong relationship. The coefficient of determination of the variable using E-wallet on the Purchasing Decision variable is 59.4%, and the coefficient of determination of the Sales Promotion variable on the Purchasing Decision variable is 43.1%.